The Impact of Recreational Long-Distance Running on the Cardiovascular System of Amateurs – Health Benefits and the Risk of Overload: A Review - Hobot, Mikołaj; Dobosz, Gabriela; Przybylska, Zuzanna; Purpura , Aleksandra; Rolski , Wiktor; Michalska, Paulina; Przystaś, Bartłomiej; Grzechowiak, Magdalena; Podeszwa, Sebastian (Quality in Sport, 2026)
Background. Long distance running has surged in popularity among recreational athletes. While moderate exercise prevents cardiovascular disease, extreme endurance events by amateurs—often lacking professional medical monitoring—raise clinical concerns regarding myocardial overload. Aim. To systematize current knowledge on the physiological benefits and potential cardiovascular risks of recreational long-distance running in amateur athletes. Material and methods. A narrative review was conducted using PubMed, Web of Science, and Scopus. We analyzed 35 peer-reviewed English articles from the last two decades focusing on amateur runners. Data extraction targeted echocardiography, cardiac magnetic resonance, and biochemical markers of myocardial injury. Results. Regular running induces favorable cardiovascular adaptations ("athlete's heart"), improving metabolic profiles and reducing all-cause mortality. Conversely, acute extreme exertion (e.g., marathons) consistently triggers transient exercise-induced cardiac fatigue (EICF) and the release of cardiac biomarkers (troponins, BNP). The right ventricle is disproportionately affected by this acute strain, whereas half-marathons induce significantly less impairment. Long-term veteran amateurs exhibit a higher prevalence of atrial fibrillation and elevated coronary artery calcification (CAC) scores; however, these plaques are predominantly calcified and stable. Conclusions. Recreational running provides substantial, dose-dependent cardiovascular benefits, but extreme distances expose amateurs to acute cardiac fatigue and chronic structural remodeling. To safely maximize outcomes, amateurs should prioritize structured recovery, distance moderation, and routine cardiovascular screening before severe events.